1987
DOI: 10.1159/000265516
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Prednisolone Succinate by Esterase in Rabbit Ocular Tissue

Abstract: Prednisolone concentrations in serum after both subconjunctival and intravenous injections of prednisolone sodium succinate at a 1 mg/kg equivalent dose of prednisolone in rabbits were analyzed by regularly phased high-performance liquid chromatography. The systemic availability after subconjunctival injection was determined to be almost 1.0 by comparing areas under the serum concentration-time curves for both administration routes. The initial hydrolytic rate of prednisolone succinate ester was dependent on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…However, it has not yet been under stood, in quantitative terms, by what kind of kinetic mechanism such steroids move from the subconjunctival injection site to the var ious tissues. Our previous study [8] demon strated that the value of the area under the serum concentration-time curve of prednis olone after subconjunctival injection of its succinate ester in rabbits was almost the same as that after intravenous administra tion of the same dose. This result demon strated that prednisolone administered subconjunctivally is absorbed almost com pletely into the systemic circulation, with a half-life of 38 min, and suggested that only a small amount of prednisolone is available to the ocular tissues.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, it has not yet been under stood, in quantitative terms, by what kind of kinetic mechanism such steroids move from the subconjunctival injection site to the var ious tissues. Our previous study [8] demon strated that the value of the area under the serum concentration-time curve of prednis olone after subconjunctival injection of its succinate ester in rabbits was almost the same as that after intravenous administra tion of the same dose. This result demon strated that prednisolone administered subconjunctivally is absorbed almost com pletely into the systemic circulation, with a half-life of 38 min, and suggested that only a small amount of prednisolone is available to the ocular tissues.…”
Section: Introductionmentioning
confidence: 84%
“…120, 240, and 360 min after injection for the 10 ntg/kg dose and 10, 60, 120, and 240 min after injection for the 0.1 mg/kg dose. At the end of each period, after sampling aqueous humor in the manner described previously [8], the animal was sacrificed via rapid injection of approximately 30 ml of air into the mar ginal vein. Following the sacrifice of each animal, approximately 700 mg of the conjunctival membrane covering the area of the injection site and both whole eyeballs was removed.…”
Section: Subconjunctival Injections and Sampling O F Ocular Tissue Anmentioning
confidence: 99%
See 2 more Smart Citations
“…PHS, a hemisuccinate ester prodrug of prednisolone (Augustijns et al, 1998), requires hydrolysis (chemical or enzymatic) of the ester bond to generate free prednisolone. The presence of esterase activity in rabbit ocular tissues has been demonstrated and well documented with ester prodrugs of pilocarpine, dipivefrin, ganciclovir, and acyclovir (Tsuji et al, 1987;Majumdar et al, 2006Majumdar et al, , 2009. Bioreversion of PHS was studied in vitreous humor and in the ocular tissues such as the cornea, iris-ciliary body, and RPE/choroid tissue as described previously (Majumdar et al, 2009).…”
Section: Animalsmentioning
confidence: 86%